Comparative petioler anatomy of tribe Mentheae subfamily Nepetoideae, Lamiaceae from Pakistan. Issue 3 (2nd September 2020) - Jehanzeb, Sahira; Zafar, Muhammad; Ahmad, Mushtaq; Sultana, Shazia; Zaman, Wajid; Ullah, Fazal
Abstract : The current study was carried out to investigate the anatomical characteristics of the petiole of eight species of tribe Mentheae collected from different phytogeographical regions of Pakistan. The transverse section was cut using Shandon Microtome (Finesse 325) to prepare slides. Cluster analysis was carried out to represent the agglomeration schedule of species viewed from the cluster point of view. The distinguishing anatomical characteristics of petioles were noted including petiole shapes, number and shape of vascular bundles, number of vessels, layers of collenchyma, and sclerenchyma . Prunella vulgaris and   Salvia plebeia were observed with sclerenchyma cells arranged outside the vascular bundle. The comparative anatomical characteristics of petiole provide valuable information in identifying the tribe Mentheae species. Petiole anatomy plays a significant role in future taxonomic and phylogenetic studies. The aim of the present study was to evaluate the taxonomical importance of the petiole anatomy in the tribe Mentheae. This work will be helpful for the taxonomist and the taxonomic importance of the petiole anatomy in this tribe specifically, and generally will provide baseline to the other studies in family Lamiaceae.